2005
DOI: 10.1179/136485905x29684
|View full text |Cite
|
Sign up to set email alerts
|

Geographical characterization of the triatomine infestations in north–central Guatemala

Abstract: In an entomological study in 2002, the degree of domestic and peridomestic infestation with triatomine bugs and the geographical distribution of such infestations were investigated in north-central Guatemala. The survey team searched for triatomines in houses constructed with mud walls or thatched roofs, in villages suspected of being infested. The level of infestation observed was lower than that seen in the same area and in eastern Guatemala, in a preliminary survey, 3 years earlier. Most of the infestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Sensor boxes and collection by householders, a combination of passive and active sampling, are cost effective, socially acceptable, and easily adaptable to community-based programs (Wisnivesky-Colli et al 1987, Chuit et al 1992, Gü rtler et al 1995, 1999. Furthermore, when infestation indices are low, such as they are after intervention, surveillance of triatomines is difÞcult, and community-based techniques often become more sensitive than inspections by trained personnel (Nakagawa et al 2005). This study found that over a sampling period of 3Ð 4 wk, the sensitivity of GN sensor boxes for sampling T. dimidiata was low and the sensitivity of manual inspection was high.…”
Section: Discussionmentioning
confidence: 96%
“…Sensor boxes and collection by householders, a combination of passive and active sampling, are cost effective, socially acceptable, and easily adaptable to community-based programs (Wisnivesky-Colli et al 1987, Chuit et al 1992, Gü rtler et al 1995, 1999. Furthermore, when infestation indices are low, such as they are after intervention, surveillance of triatomines is difÞcult, and community-based techniques often become more sensitive than inspections by trained personnel (Nakagawa et al 2005). This study found that over a sampling period of 3Ð 4 wk, the sensitivity of GN sensor boxes for sampling T. dimidiata was low and the sensitivity of manual inspection was high.…”
Section: Discussionmentioning
confidence: 96%
“…In spite of the fact that T. ryckmani has not been found infected with T. cruzi under natural conditions (Marroquín et al 2004a, Monroy et al 2004, Marín et al 2006, the species is able to colonize chicken coops, sometimes in elevated numbers, up to 369 in a single coop (Nakagawa et al 2005). It also has been found colonizing houses, in smaller quantities, and adults are also found visiting houses in domestic and peridomestic environments, both in Nicaragua and Guatemala (Monroy et al 2004, Nakagawa et al 2005, Marín et al 2006.…”
Section: Discussionmentioning
confidence: 98%
“…It also has been found colonizing houses, in smaller quantities, and adults are also found visiting houses in domestic and peridomestic environments, both in Nicaragua and Guatemala (Monroy et al 2004, Nakagawa et al 2005, Marín et al 2006. Now that we know that this species becomes easily infected with T. cruzi in the laboratory, its natural infection could be predicted and its epidemiological role in the transmission of Chagas disease in Central American countries needs to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative control intervention strategies, based on the Ecohealth principles, have recently been implemented at different pilot scales [15, 16, 25] and are currently giving promising results (Waleckx et al, unpublished data). While T. dimidiata generally does not establish colonies inside human dwellings in the Yucatán Peninsula, in other parts of its geographical distribution, such as in Guatemala, populations are well domiciliated, as evidenced by bug collections throughout the country showing high infestation and colonization indexes [10, 26]. …”
Section: Discussionmentioning
confidence: 99%